"Kankakee": An Old Etymological Puzzle. (June 2014) - McCafferty, Michael
<x content-type="archive" xml:space="preserve">Abstract</x> A clean linguistic analysis of a place name as important in history and geography as "Kankakee" is presented here. The original place name, from the Miami-Illinois language, while faithfully recorded in the early 1680s by the explorer René de La Salle, was distorted by the French in the years that followed. This article explains the original form of this place name and its development into the form "Kankakee." It even shows how aspects of the original Indian and French pronunciation of the name are still with us in the English pronunciation of this name.